AKUNTABILITAS DAN AKSESIBILITAS PENGELOLAAN DANA DESA PADA DESA MANDALLE - Wiyana, Anim; Nurmaulidah, Nurmaulidah (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2024)
The aim of this research is to look at the influence of Accountability and Accessibility on Village Fund Management in Mandalle Village, West Bajeng District, Gowa Regency, South Sulawesi Province. The research method applied was quantitative with a total sample of 67 people consisting of village officials, RT Head, RW Head, Village Supervisory Board and Youth Leaders in Mandalle Village, Gowa Regency, South Sulawesi. The results of the questionnaire obtained were tested for validity and reliability as well as classic assumptions in the form of normality assumptions, then data analysis was carried out using multiple linear regression techniques. Based on the findings in several tests, it is clear that accountability has a positive and significant effect on village fund management, but accessibility has no effect on village fund management. The implementation of accountability in Mandalle Village has been carried out optimally because there is an announcement banner containing the contents of the financial report for one year of government in front of the Mandalle Village office. In developing the accessibility of village fund management information, the Mandalle Village Government needs access to social media and the Mandalle Village website.